Development and Validation of a Motor Skills Learning Model for Pencak Silat Athletes Aged 15–18 Years - Hani Fatonah; Sujarwo Sujarwo; Widiastuti Widiastuti (Sriwijaya University Learning and Education International Journal, 2024)
The purpose of this study was to evaluate the effectiveness of a machete skills learning model for Pencak Silat athletes aged 15–18 years by collecting empirical evidence regarding its outcomes. This study employed a Research and Development (R&D) approach combined with a pre-test–post-test experimental design. Data were analyzed using an independent samples t-test with SPSS software to determine the effectiveness of the developed learning model. The effectiveness test involved 75 Pencak Silat athletes aged 15–18 years from Ciomas District, Serang Regency, Banten Province, Indonesia. The participants received the intervention over 16 training sessions using the developed machete skills learning model. Performance was assessed using a standardized machete skills test that measured the accuracy and execution of deep strikes and deep slashes. The experimental group showed an improvement in mean scores from 0.22806 on the pre-test to 0.23786 on the post-test. Similarly, the control group improved from 0.60788 to 0.65368. Statistical analysis revealed a significant difference between the experimental and control groups (p = 0.003, p < 0.05), indicating that the learning model produced a significantly greater improvement than conventional training methods. These findings demonstrate that the developed machete skills learning model is effective in improving the machete skills of beginner Pencak Silat athletes aged 15–18 years and can be recommended as an alternative training model for coaches and practitioners.